2015
DOI: 10.1248/bpb.b15-00396
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory Role of Early Ca<sup>2+</sup> Responses in H<sub>2</sub>O<sub>2</sub>-Induced β-Cell Apoptosis

Abstract: Our previous study using apoptosis analysis suggested that Ca 2 release through inositol 1,4,5-trisphosphate (IP 3 ) receptors and the subsequent Ca 2 influx through store-operated channels (SOCs) constitute a triggering signal for H 2 O 2 -induced β-cell apoptosis. In the present study, we further examined the obliga-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…H 2 O 2 has been shown to induce cell apoptosis, where p16 plays a crucial role616. Given a correlation between apoptosis and p16 phosphorylation was observed, we asked whether H 2 O 2 could influence the phosphorylation of p16.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 has been shown to induce cell apoptosis, where p16 plays a crucial role616. Given a correlation between apoptosis and p16 phosphorylation was observed, we asked whether H 2 O 2 could influence the phosphorylation of p16.…”
Section: Resultsmentioning
confidence: 99%
“…ROS may be the first-stage initiators inducing neuron apoptosis or act as a signal in apoptotic cascade2324. As a typical ROS, hydrogen peroxide (H 2 O 2 ) is widely used as an apoptosis inducer16. It has been shown that H 2 O 2 induced DNA damage and apoptosis in human neuroblastoma SK-N-MC cells25.…”
Section: Discussionmentioning
confidence: 99%
“…Although cytosolic H 2 O 2 concentrations produced by oxidative stress in pancreatic acinar cells is not known, only small proportion of cells (34%) were response to 100 µM of H 2 O 2 and most cells (97%) were response to 300 µM of H 2 O 2 in the present study. In general, H 2 O 2 at concentrations from 10 µM to 1 mM caused intracellular Ca 2+ accumulation in various cell types [1011,12,13,14,15,16,17]. These results suggest that excess generation of oxidants in pathologic conditions could disturb Ca 2+ homeostasis mediated by sulfhydryl group oxidation in pancreatic acinar cells.…”
Section: Discussionmentioning
confidence: 98%
“…Although oxidant-induced intracellular Ca 2+ overload has been revealed in various cell types, the underlying mechanisms of Ca 2+ mobilization and elimination are complicated [1011,12,13,14,15,16,1718]. It has been known that the involvement of oxidants in Ca 2+ homeostasis is mediated by the modification of disulfide bonds between cysteine residues of Ca 2+ regulating proteins including SERCA, PMCA and Na + /Ca 2+ exchanger (NCX) [3132].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation